2014
DOI: 10.15740/has/au/9.4/558-561
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of front line demonstrations on the yield of transplanted rice

Abstract: The rice (Oryza sativa) covers largest area in total grain production in Narmada district of Gujarat. One of the major constraints of low productivity of rice is lack of newly generated technology among farmers. A total of 54 front line demonstrations were conducted during 2012 to 2013 on area of 9.0 ha with the active participation of farmers with the objective to demonstrate the latest variety technology of rice production. The percentage increase in the yield over local check was 20.4 with higher gross retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 0 publications
27
19
0
Order By: Relevance
“…Regarding the method of fertilization, under demonstration, all fertilizers were applied at the time of sowing, whereas, under farmers' practice, broadcast method of fertilization was adopted. Similar findings have also been observed by Raj et al, (2013).…”
Section: Differences Between Farmers' Practices and Technology Demonssupporting
confidence: 90%
See 2 more Smart Citations
“…Regarding the method of fertilization, under demonstration, all fertilizers were applied at the time of sowing, whereas, under farmers' practice, broadcast method of fertilization was adopted. Similar findings have also been observed by Raj et al, (2013).…”
Section: Differences Between Farmers' Practices and Technology Demonssupporting
confidence: 90%
“…However more variations in yield was recorded in farmers practices as compared to demonstration. Similar yield enhancement in different crops in front line demonstration has been documented by Raj et al, (2013). It is evident from the results that the yield of improved YVM resistance variety was found better than the local check under same environment conditions.…”
Section: The Performance Of Fld Programme On Production and Economicssupporting
confidence: 79%
See 1 more Smart Citation
“…43184 and Rs.39800 as against to farmers practices i.e., Rs.16261, 18558 and 18373 per hectare during the years 2013-14,2014-15 and 2015-16, respectively (Table 3). Similar results were corroborated with Singh et al, 2014 andRaj et al, 2013 findings. The Benefit: Cost ratio of pigeon pea during 2013-14, 2014-15 and 2015-16 under improved cultivation practices were 2.02, 2.30 and 2.51, respectively while it was 1.49, 1.42 and 2.03 under farmers practice for the respective years.…”
Section: Resultssupporting
confidence: 92%
“…The findings confirm with the findings of Yadav et al (2007) and Meena et al (2011) and Meena and Singh (2017) who found more yield in pulses under FLD plots. Seed yield (kg/ha): The productivity of greengram under improved production technology ranged between 920-1045 kg/ha with mean yields of 982 kg/ha and overall production 2945 kg/ha in three years (Table 3) Raj et al (2013) and Meena and Singh (2017). They found more gain yield of FLD plots than the existing practices.…”
Section: Methodsmentioning
confidence: 99%